Let's start by simplifying both sides of the equation.
8x - 2(x + 1) = 2(3x - 1)
First, distribute the -2 in the left side:
8x - 2x - 2 = 2(3x - 1)
The left side becomes:
6x - 2 = 2(3x - 1)
Now distribute the 2 in the right side:
6x - 2 = 6x - 2
Now, add 2 to both sides of the equation:
6x - 2 + 2 = 6x - 2 + 2
This simplifies to:
6x = 6x
The equation becomes:
6x = 6x
This means that the equation is true for any value of x. So, the solutions to the equation are all real numbers.
8x-2(x+1)=2(3x-1)
1 answer